Ultrasound-guided peri-brachial plexus polydeoxyribonucleotide injection for a patient with postherpetic brachial plexopathy: A case report. Issue 31 (August 2019) - Kim, Jun Young; Hwang, Jong-Moon; Park, Jin-Sung; Park, Sungwon; Lee, Byung Joo; Park, Donghwi
Abstract: Rationale: Although most complications of herpes zoster (HZ) are associated with the spread of varicella-zoster virus from the initially involved sensory ganglion, motor nerve impairment, such as limb weakness, is a rare but severe complication that is difficult to treat. Patient concern: A 73-year-old female presented with sudden left upper limb pain and weakness after HZ. Diagnosis: Brachial plexopathy following HZ (postherpetic brachial plexopathy). Intervention: Despite alleviation of the vesicles with antiviral treatments, the left upper limb weakness and neuropathic pain did not improve. After obtaining patient's consent, ultrasound-guided polydeoxyribonucleotide (PDRN) injection was performed around the left brachial plexus. Outcomes: The patient showed marked improvement in left arm pain from numerical rating scale (NRS) 9 to 4, 1 day after PDRN injection. Subsequently, the pain improved to NRS 3, and motor weakness improved to Medical Research Council grade 2 to 4. Lessons: PDRN can be considered a viable substitute for corticosteroid injection in treatment of motor weakness and neuropathic pain after HZ.